MODELS OF INFOMATIONAL DECISION SUPPORT FOR THE COMPLEX INFORMATION SECURITY MANAGMENT - Dudatyev, A. V.; Voitovych, O. P. (Radio Electronics, Computer Science, Control, 2017)
Context. The existence of a competitive information environment, which is a specific arena for special information operations, shows the necessity for implemention of information resources complex protection. Information warfare and the problems, those arise in the field of complex information security management, determine the relevance of the information decision support models development, as well as the creation of situational or information-analytical centers of the complex information security at the «Enterprise – Region – State» management levels. Objective. The goal of this research is a development of information decision support model of the complex information security management of the multi-level socio-technical system which is consists of the individual objects, groups of objects (region) and the State en block, which would provide security level quantitative indicators as well as the ability to make decisions for the complex information security at the «Enterprise – Region – State» levels management. Method. The method of this research is based on the idea that the State protection level depends on the subordinate regions protection level, which in its turn, depends on the subordinate local objects (enterprise) protection level. The enterprise protection level depends on the violation of at least one of the criteria: integrity, availability, confidentiality. Results. The task of developing of the generalized model for complex information security of the multi-level socio-technical system evaluation in terms of «Enterprise – Region – State» is solved, which allows obtaining an protection level estimation of the both local (enterprise) and integrated (region and the State) objects. The probabilistic or expert evaluations in the form of fuzzy sets can be used for base threat occurrence estimation. The structural model of multi-level information-analytic center of the complex information security management is proposed. The results of researching have shown the possibility of using this approach for estimation and management problem solution of information security management for complex information security of the multi-level socio-technical systems. Conclusions. Scientific novelty of the research is in the fact that the complex information security at the «Enterprise – Region – State» management levels evaluation model is proposed for the first time. Practical significance consists in the development of the software implemented the process of complex information security of the multilevel socio-technical systems evaluation in terms of «Enterprise – Region – State» analyzing and estimation, as well as the synthesis of management decisions based on the generated knowledge bases.